2019
DOI: 10.18203/2320-1770.ijrcog20195305
|View full text |Cite
|
Sign up to set email alerts
|

Maternal factors affecting outcome of induction of labour

Abstract: Background: Induction of labour is a common procedure in modern obstetrics and accounts for 20% among all deliveries. This study aims to assess the factors associated with success/failure of induction of labour.Methods: This is a cohort study involving 220 women who underwent induction of labour in the department of obstetrics and gynaecology, MGMCRI from December 2016 to May 2018. After obtaining informed consent, patients were recruited into the study. Maternal parameters like age, parity, gestational age, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This finding was supported by studies conducted in Ethiopia ( 2 , 28 30 ). Similarly, a study was done by Devarasetty et al revealed that vaginal delivery after induction was high in pregnant women with a Bishop score ≥5 before induction ( 34 ). A high Bishop score means that there is a greater chance that an induction will be successful.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This finding was supported by studies conducted in Ethiopia ( 2 , 28 30 ). Similarly, a study was done by Devarasetty et al revealed that vaginal delivery after induction was high in pregnant women with a Bishop score ≥5 before induction ( 34 ). A high Bishop score means that there is a greater chance that an induction will be successful.…”
Section: Discussionmentioning
confidence: 82%
“…This finding was in line with 25.4% in four teaching hospitals of Addis Ababa, Ethiopia ( 29 ), 21.4% in Jimma specialized hospital, Ethiopia ( 2 ), and 24.1% in Catholic Maternity Hospital, Nigeria ( 32 ). But it was lower than 29.5% in two public hospitals of Mekelle town, Ethiopia ( 30 ), 42.1% in Wolliso St. Luke Catholic hospital, Ethiopia ( 28 ), and 43.6% in Mahatma Gandhi Medical College and Research Institute Hospital, India ( 34 ). The variation observed could be due to the methods used during the induction of labor.…”
Section: Discussionmentioning
confidence: 96%